2007
DOI: 10.1016/j.ejor.2005.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Modelling imperfect advance demand information and analysis of optimal inventory policies

Abstract: We consider an inventory control problem where it is possible to collect some imperfect information on future demand. We refer to such information as imperfect Advance Demand Information (ADI), which may occur in different forms of applications. A simple example is a company that uses sales representatives to market its products, in which case the collection of sales representatives' information as to the number of customers interested in a product can generate an indication about the future sales of that prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…This outcome is again in line with earlier findings (e.g. Bourland et al 1996, Tan et al 2007). In general, holding a safety stock is found to be more effective than buffering in a safety lead time in coping with ADI unreliability.…”
Section: The Effect Of Demand Uncertaintysupporting
confidence: 82%
See 2 more Smart Citations
“…This outcome is again in line with earlier findings (e.g. Bourland et al 1996, Tan et al 2007). In general, holding a safety stock is found to be more effective than buffering in a safety lead time in coping with ADI unreliability.…”
Section: The Effect Of Demand Uncertaintysupporting
confidence: 82%
“…The papers that do study demand uncertainty relate uncertainty to due-date setting (Tan et al 2007), order cancellations (Thonemann 2002, Tan et al 2007), incomplete order data on product type (Thonemann 2002) or partial schedules, where part of the orders are still unknown . We could only find the combination of variability in supply and unreliability in demand in papers by Hu et al (2003Hu et al ( , 2004 and by Toktay and Wein (2001).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…If it is certainly going to happen then it is called perfect ADI, otherwise it is called as imperfect ADI. It may be generated through internet retailing or from sales representatives (Tan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The model created by Tan et al (2007) also indicated that the optimal ordering policy is also an order-up-to system based on the kind of demand information supplied by a VMI system. Yao et al (2007) also evaluated the effect of implementing VMI on inventory-carrying costs.…”
Section: Theoretic Mathematical Modelsmentioning
confidence: 99%